Biogeochemical evidence of Holocene East Asian summer and winter monsoon variability from a tropical maar lake in southern China. (1st March 2015) - Jia, Guodong; Bai, Yang; Yang, Xiaoqiang; Xie, Luhua; Wei, Gangjian; Ouyang, Tingping; Chu, Guoqiang; Liu, Zhonghui; Peng, Ping'an
Abstract: Lake Huguangyan (21°9′ N, 110°17′ E), a maar lake located near the South China Sea, can provide valuable sedimentary data regarding past changes of the East Asian monsoonal system. Here, we used the proxies of TOC, δ 13 Corg, δ 15 N, and leaf wax n -alkane δ 13 C values (δ 13 Cwax ) to reconstruct the lake conditions, which, in turn, revealed patterns in monsoonal changes during the Holocene. Two distinct patterns of proxy changes were identified in the sedimentary profile. A marked shift in the δ 13 Cwax value at ∼9.2 ka (thousand years ago) suggests the abrupt disappearance of C4 plants, signaling the enhancement of East Asian summer monsoon (EASM). Between 9.2 and 1.8 ka, a nearly pure C3 terrestrial ecosystem was present, with the climax at ca 7–6 ka. After ca 3 ka, fewer tropical species and a reappearance of C4 plants at 1.8 ka indicate a weakened EASM in the late Holocene. The TOC concentration and δ 15 N value proxies appear to be associated with lake aquatic production and upwelled nutrient supply and utilization, which are modulated by, and thus indicative of, the strength of the East Asian winter monsoon (EAWM). The two EAWM records suggest a weakening trend from the early to late Holocene, with the most significant transition at ∼6 ka; thus, the EAWM trend was broadly in-phase with that of the EASM. However, the marked EASM intensification at 9.2 ka occurred within the period of a strong EAWM between 10.5 and 6 ka and lagged the monsoonal enhancement as inferred from the Dongge Cave δ 18 O values. Our EASM records displays an overall arid-wet-arid pattern, which is in-phase with the hydrological variability in tropical Australia and anti-phase with that in the outer-tropical Andes. These phase relationships might be linked to changes in the thermal state of the tropical Pacific during the Holocene. Highlights: Abrupt C4 plant vanishing and lake level rise at ∼9.2 ka due to intensified EASM. Less tropical species and C4 plant reappearance in late Holocene. TOC and δ 15 N suggest declining EAWM from early to late Holocene. Millennial changes in EASM are linked to mean ENSO state.